Chronic pain acceptance incrementally predicts disability in polytrauma-exposed veterans at baseline and 1-year follow-up. (October 2015) - Cook, Andrew J.; Meyer, Eric C.; Evans, Lianna D.; Vowles, Kevin E.; Klocek, John W.; Kimbrel, Nathan A.; Gulliver, Suzy Bird; Morissette, Sandra B.
Abstract: War veterans are at increased risk for chronic pain and co-occurring neurobehavioral problems, including posttraumatic stress disorder (PTSD), depression, alcohol-related problems, and mild traumatic brain injury (mTBI). Each condition is associated with disability, particularly when co-occurring. Pain acceptance is a strong predictor of lower levels of disability in chronic pain. This study examined whether acceptance of pain predicted current and future disability beyond the effects of these co-occurring conditions in war veterans. Eighty trauma-exposed veterans with chronic pain completed a PTSD diagnostic interview, clinician-administered mTBI screening, and self-report measures of disability, pain acceptance, depression, and alcohol use. Hierarchical regression models showed pain acceptance to be incrementally associated with disability after accounting for symptoms of PTSD, depression, alcohol-related problems, and mTBI (total adjusted R 2 = .57, p < .001, ΔR 2 = .03, p = .02). At 1-year follow-up, the total variance in disability accounted for by the model decreased (total adjusted R 2 = .29, p < .001), whereas the unique contribution of pain acceptance increased ( ΔR 2 = .07, p = .008). Pain acceptance remained significantly associated with 1-year disability when pain severity was included in the model. Future research should evaluate treatments that address chronic pain acceptance and co-occurring conditions to promote functional recovery in the context of polytrauma in war veterans. Highlights: Chronic pain acceptance incrementally predicted disability in returned war veterans. PTSD, depression, alcohol problems, mild TBI, and pain severity were accounted for in the analyses. Predictive strength of chronic pain acceptance was greater for disability at 1-year.